2015
DOI: 10.5539/ibr.v8n3p42
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Variety Seeking: From an Information Perspective

Abstract: Variety seeking is one of the most common psychological heuristics when consumers make decisions. The literature posits that understanding the mechanism of variety seeking is critical to explain consumers' decision-making process. Yet little is known about the effects of information, which also significantly influences consumers' choice behavior. Drawing on established theories of psychology and economics, the author develops a synergetic framework investigating the impact of information adequacy on degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The type of reviews on purchase intention is stronger for experts than for novices, while the effect of the number of reviews on purchase intention is stronger for novices than experts (Boon and Park and Kim, 2008). The main difference between experts and novices customers is the way they use obtainable information from market communication process, even the information content stays the same (Ju, 2015). Moreover, when information is limited, Ju (2015) found that novice customers are more likely to prefer variety than expert customers.…”
Section: Experts Vs Novicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The type of reviews on purchase intention is stronger for experts than for novices, while the effect of the number of reviews on purchase intention is stronger for novices than experts (Boon and Park and Kim, 2008). The main difference between experts and novices customers is the way they use obtainable information from market communication process, even the information content stays the same (Ju, 2015). Moreover, when information is limited, Ju (2015) found that novice customers are more likely to prefer variety than expert customers.…”
Section: Experts Vs Novicesmentioning
confidence: 99%
“…Customer with different expertise, usually categorized as experts and novices (Park, 1980;Raju et al, 1995;Ju, 2015). As a combination of product knowledge and experience (Yale and Gilly, 1995), customer expertise influences the way they collect and organize information (Lee, 2014).…”
Section: Experts Vs Novicesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ju (2015), variety-seeking is a common psychological heuristic employed by consumers when making decisions. In variety-seeking behaviour, consumer engagement tends to be limited as consumers frequently switch between brands.…”
Section: Variety Seeking Behaviourmentioning
confidence: 99%